Electro-catalytic hydrogen evolution catalyst taking alloy as active metal as well as preparation method and application of electro-catalytic hydrogen evolution catalyst

By using the hydrothermal method to prepare copper silicate support and the precious metal and non-precious metal nanoparticle alloy catalysts supported by the reduction method in electrolytic hydrogen production technology, the energy consumption problem caused by overpotential in electrolytic hydrogen production technology is solved, and an efficient and energy-saving hydrogen precipitation effect is achieved.

CN119640304APending Publication Date: 2025-03-18FUZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411860725.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing electrolytic hydrogen production technology, the overpotential of cathode hydrogen evolution and anode oxygen evolution leads to an increase in actual energy consumption, limiting the development of this technology in the engineering field.

Method used

The copper silicate support was prepared by hydrothermal method, and the precious metal and non-precious metal nanoparticles were supported by the reduction method to form an alloy catalyst. The catalyst fixes precious metal and non-precious metal nanoparticles on the surface through the large specific surface area and mesoporous structure of the copper silicate material, increasing the reaction area of ​​the catalyst and improving the hydrogen evolution activity.

Benefits of technology

It effectively prevents the loss of precious metal nanoparticles, improves its dispersion and hydrogen evolution efficiency, and has excellent hydrogen evolution activity at low noble metal loads, good durability, which is significantly better than commercial 20wt%Pt/C catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640304A_ABST
    Figure CN119640304A_ABST
Patent Text Reader

Abstract

The invention discloses an electro-catalytic hydrogen evolution catalyst taking an alloy as an active metal and a preparation method and application thereof, SiO2 is prepared by a hydrothermal method, CuSiOx is formed by doping Cu, and finally non-noble metal is loaded and is replaced and reduced by noble metal or a reducing agent is added to form an alloy which is loaded on the CuSiOx. The CuSiOx has a large specific surface area and can effectively load an alloy formed by non-noble metal and noble metal, the dispersity of the CuSiOx is greatly improved, the reaction area of the catalyst is increased due to the porous structure, and the hydrogen evolution activity of the catalyst is improved. The catalyst has excellent hydrogen evolution activity when the loading capacity of precious metal is low, the overpotential is 24 mV when the current density is 10 mA / cm < 2 >, and after 1000 times of volt-ampere cycle tests, the overpotential can still be kept at 25 mV and is better than that of a 20 wt% Pt / C catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrocatalytic hydrogen evolution catalyst with an alloy as an active metal and a preparation method and application thereof, belonging to the technical field of hydrogen production by electrolysis of water. Background Art

[0002] The electrolysis of water process is easy to industrialize due to its high efficiency. It is the most promising method for hydrogen production, with the characteristics of simple operation, high product purity, no pollution and economical raw material sources. Electrolysis of water is to pass direct current through an acidic or alkaline aqueous solution to decompose water, precipitating hydrogen at the cathode and oxygen at the anode. The theoretical voltage required for water electrolysis is 1.23V, which is temperature-dependent. However, in actual applications, the voltage required to decompose water is higher than the theoretical value. The additional voltage required is the overpotential. The overpotential of hydrogen evolution at the cathode and oxygen evolution at the anode will lead to an increase in actual energy consumption, which has become a bottleneck restricting the development of electrolysis of water in the engineering field. Therefore, it is necessary to reduce the overpotential to make the water decomposition reaction more energy-efficient and efficient.

[0003] As the most critical link in the water electrolysis system, the preparation of HER and OER electrodes with high catalyst activity is the key to reducing the high electrode overpotential. Therefore, it is of great theoretical and practical significance to study and develop electrocatalytic electrode materials that can reduce the energy consumption of water electrolysis. So far, among various electrode materials, Pt electrode has the best catalytic hydrogen evolution activity, but its scarce reserves and high cost limit its large-scale application. Therefore, the development of electrode materials with high hydrogen evolution activity and low precious metal loading is a hot topic in current research.

[0004] After long-term and extensive research, the inventor of the present invention prepared a copper silicate carrier by a hydrothermal method, and then loaded precious metal and non-precious metal nanoparticles by a reduction method to form an alloy. The precious metal and non-precious metal nanoparticles are fixed on the surface and composited with copper silicate by the large specific surface area and mesoporous structure of the copper silicate material. The copper silicate material in the present invention can effectively prevent the loss of precious metal nanoparticles and greatly improve its dispersibility, and its two-dimensional mesoporous structure increases the reaction area of ​​the catalyst, further improving the hydrogen evolution activity of the catalyst, and has great economic and social value. Summary of the invention

[0005] The present invention aims to provide an electrocatalytic hydrogen evolution catalyst with an alloy as an active metal, wherein CuSiO x The catalyst is used as the carrier, and the alloy of precious metal and non-precious metal is the active metal; based on the catalyst, the content of the alloy is 1-35wt%, more preferably 15-30wt%, and the mass ratio of precious metal to non-precious metal in the alloy is 1:0.05-1:10; the particle size of the alloy is 0.3-50 nm, and the particle size of the catalyst is 100 nm.

[0006] Another object of the present invention is to provide a method for preparing an electrocatalytic hydrogen evolution catalyst in which an alloy is an active metal, comprising the following steps: (1) Preparation of SiO2 nanospheres; (2) Add the SiO2 nanospheres prepared in step (1) into deionized water, then add copper salt, stir, heat, and keep warm for 5-20 hours, then filter, wash, and dry to obtain the product CuSiO x .

[0007] (3) The CuSiO prepared in step (2) x Dispersed in a solvent, then adding a non-precious metal precursor, stirring and heating for 1-10 hours to reduce it and load the non-precious metal on CuSiO x , then filter, wash and dry.

[0008] (4) Dispersing the product obtained in step (3) in deionized water, adding a noble metal precursor, stirring and heating for 1-10 hours, performing replacement reduction on the non-noble metal element or adding a reducing agent to reduce it to form an alloy, and then filtering, washing, and drying.

[0009] (5) dispersing the product obtained in step (4) in an acid solution and stirring for 1 to 24 hours, then filtering, washing, and drying to obtain the electrocatalytic hydrogen evolution catalyst.

[0010] Furthermore, the preparation method of SiO2 in step (1) comprises the following steps: stirring an organic solvent, deionized water and ammonia water, adding a silicon source and stirring for 5-50 hours, then filtering, washing and drying to obtain the product SiO2. The organic solvent comprises one of ethanol, ethylene glycol and acetone; and the silicon source comprises one of tetraethyl silicate, sodium silicate and ethyl metasilicate.

[0011] Furthermore, the non-metal precursor in step (3) includes nitrate, acetylacetonate, sulfate, hydrochloride, perchlorate of a non-noble metal, and the non-noble metal precursor and CuSiO x The mass ratio is 200:1-0.02:1.

[0012] Furthermore, the solvent described in step (3) includes water, methanol, ethanol, ethylene glycol, glycerol, acetone, etc., and mixtures thereof in any proportion.

[0013] Furthermore, the noble metal precursor described in step (4) includes acetylacetonate, nitrate, chloride, chloroplatinic acid, chloroauric acid, and chloropalladic acid of the noble metal.

[0014] Furthermore, the acid in step (5) includes one or more of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, hypochlorous acid, and hydrofluoric acid. The solvent of the acid solution includes a mixture of one or more of water, methanol, ethanol, ethylene glycol, pentanediol, isopropanol, glycerol, acetone, and butanol. The concentration of the acid is 0.1-10 mol / L.

[0015] Application: The alloy is used as an active metal catalyst in the electrolysis of water to produce hydrogen.

[0016] The present invention prepares a copper silicate carrier by a hydrothermal method, and then loads precious metal and non-precious metal nanoparticles by a reduction method to form an alloy. Precious metal and non-precious metal nanoparticles are fixed on the surface and composited with copper silicate by the large specific surface area and mesoporous structure of the copper silicate material. The copper silicate material in the present invention can effectively prevent the loss of precious metal nanoparticles and greatly improve its dispersibility, and its two-dimensional mesoporous structure increases the reaction area of ​​the catalyst, further improving the hydrogen evolution activity of the catalyst. Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention uses CuSiO x The mesoporous structure of the nanoparticles binds the precious metal nanoparticles in the mesoporous structure, effectively preventing their growth and loss, and greatly improving the dispersion of the precious metal nanoparticles and the efficiency of hydrogen evolution.

[0017] (2) The present invention uses copper silicate as a base material and coats non-precious metals and precious metal alloys to increase the specific surface area and improve the hydrogen evolution activity of the catalyst. The catalyst obtained by the present invention has excellent hydrogen evolution activity at a low precious metal loading. 2 The overpotential is 24mV, and after 1000 volt-ampere cycle tests, the overpotential can still be maintained at 25mV, which is significantly better than commercial 20wt%Pt / C. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is a scanning electron microscope (SEM) image of the electrocatalytic hydrogen evolution catalyst prepared by the present invention; Figure 2 The figure is a cyclic voltammetric polarization (LSV) curve of the electrocatalytic hydrogen evolution catalyst prepared by the present invention. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 Preparation of 25wt% PtCu / CuSiO x Electrocatalytic hydrogen evolution catalyst (1) 50 mL of ethanol and 30 mL of deionized water were mixed, and then 1.65 mL of 28 wt.% ammonia water was added and stirred for 10 minutes. Then, 70 mg of sodium silicate was added dropwise and stirred continuously for 24 hours. Finally, the solution was centrifuged at 12,000 rpm for 10 minutes to obtain particles, which were washed three times with deionized water and dried at 60°C for 12 hours to obtain SiO2 nanospheres; 0.13 g of SiO2 nanospheres were ultrasonically dispersed in 20 mL of deionized water for use, 0.17 g of copper nitrate trihydrate and 30 mL of deionized water were added to a beaker and stirred until the copper nitrate trihydrate was completely dissolved, then 5 mL of 28 wt.% ammonia water was added dropwise and stirred for 5 minutes, the completely dispersed silica sphere solution was poured into a beaker and stirred for 10 minutes, and the obtained solution was ultrasonically treated for 10 minutes and then poured into 100 mL of polytetrafluoroethylene liner. The inner tank was placed in a reactor, heated to 140°C, kept warm for 10 hours, and freeze-dried to obtain CuSiO x Material, CuSiO x The pore size of the material is 2-4 nm and the specific surface area is 521.79 m 2 g -1 .

[0021] (2) Take 100 mg of the obtained CuSiO x Disperse 76.5 mg of copper nitrate trihydrate in 100 ml of ethylene glycol and stir to mix CuSiO x Dissolve completely with copper nitrate trihydrate for 10 min, and then use ultrasound to dissolve CuSiO x The sample was completely dispersed for 10 minutes. Heat to 210 ° C in an oil bath and reflux for 30 minutes, then cool to room temperature. The solution was filtered and rinsed with deionized water three times, dried and taken out, 100 mg of the prepared sample was placed in a 50 mL flask, and 35 mL of deionized water was added to ultrasonically disperse for 10 minutes. While magnetically stirring, 0.1M-0.4M chloroplatinic acid solution was dropped. Among them, Pt and CuSiO x The mass ratio of was 0.15:1. The obtained solution was dispersed by ultrasonic for 10 minutes, stirred at 60 ° C for 6 hours, and the obtained sample was filtered and washed 3 times. Then the sample was dissolved in 30 mL of 1 M nitric acid solution, slowly stirred for 24 hours, centrifuged, washed with deionized water and ethanol several times, and freeze-dried to obtain PtCu / CuSiO x Electrocatalytic hydrogen evolution catalyst; wherein the PtCu alloy accounts for 25wt% of the total catalyst, and the mass ratio of Pt to Cu in the PtCu alloy is 1:0.55, recorded as 25wt% PtCu / CuSiO x Electrocatalytic hydrogen evolution catalyst; Figure 1 The SEM image of the obtained catalyst is Figure 1 It can be seen that the obtained catalyst has a smaller nanosize.

[0022] Example 2 Preparation of 25wt% PdFe / CuSiO x Electrocatalytic hydrogen evolution catalyst (1) 50 mL of ethylene glycol and 30 mL of deionized water were mixed, and then 1.65 mL of 28 wt.% ammonia water was added and stirred for 10 minutes. Then, 7 mL of tetraethyl orthosilicate (TEOS) was added dropwise and stirred continuously for 24 hours. Finally, the solution was centrifuged at 12,000 rpm for 10 minutes to obtain particles, which were washed three times with deionized water and dried at 60 °C for 12 hours to obtain SiO2 nanospheres; 0.13 g of SiO2 nanospheres were ultrasonically dispersed in 20 mL of deionized water for later use, 0.51 g of copper sulfate and 30 mL of deionized water were added to a beaker and stirred until copper nitrate trihydrate was completely dissolved, and then 5 mL of 28 wt.% ammonia water was added dropwise and stirred for 5 minutes, the completely dispersed silica sphere solution was poured into a beaker and stirred for 10 minutes, and the obtained solution was ultrasonically treated for 10 minutes and then poured into 100 mL of polytetrafluoroethylene liner. The inner tank was placed in a reactor, heated to 140 °C, kept warm for 10 hours, and freeze-dried to obtain CuSiO x Material, CuSiO x The pore size of the material is 2-4nm and the specific surface area is 521.79m 2 g -1 .

[0023] (2) Take 100 mg of the obtained CuSiO x Disperse with 10 mL of 0.5 mol / L ferric nitrate solution in 100 ml of ethylene glycol, heat to 100 °C in an oil bath and reflux for 30 minutes, add 10 mL of hydrazine hydrate and 10 mL of 28 wt.% ammonia water in turn, stir evenly and let stand for 5 min, then cool to room temperature. Filter the solution and rinse with deionized water three times, dry and take out, then put 100 mg of the prepared sample into a 50 mL flask, add 35 mL of deionized water and ultrasonically disperse for 10 minutes. While magnetically stirring, drop 0.1 M palladium chlorate aqueous solution. Among them, palladium and CuSiO x The mass ratio of was 0.15:1. The obtained solution was dispersed by ultrasonic for 10 minutes, and 100 mg of sodium borohydride was added. After heating to 200 °C, it was filtered, washed and dried. Then the sample was dissolved in 30 mL of 1 M nitric acid solution, slowly stirred for 24 h, centrifuged, washed with deionized water and ethanol several times, and freeze-dried to obtain PdFe / CuSiO xElectrocatalytic hydrogen evolution catalyst; wherein the PdFe alloy accounts for 25wt% of the total catalyst, and the mass ratio of Pd to Fe in the PdFe alloy is 1:0.8, recorded as 25wt% PdFe / CuSiO x Electrocatalytic hydrogen evolution catalyst.

[0024] Example 3 Preparation of 25wt% AuNi / CuSiO x Electrocatalytic hydrogen evolution catalyst (1) 50 mL of acetone and 30 mL of deionized water were mixed, and then 1.65 mL of 28 wt.% ammonia water was added and stirred for 10 minutes. Then, 13 mL of ethyl metasilicate was added dropwise and stirred continuously for 24 hours. Finally, the solution was centrifuged at 12,000 rpm for 10 minutes to obtain particles, which were washed three times with deionized water and dried at 60°C for 12 hours to obtain SiO2 nanospheres; 0.13 g of SiO2 nanospheres were ultrasonically dispersed in 20 mL of deionized water for use, 0.17 g of copper nitrate trihydrate and 30 mL of deionized water were added to a beaker and stirred until the copper nitrate trihydrate was completely dissolved, then 5 mL of 28 wt.% ammonia water was added dropwise and stirred for 5 minutes, the completely dispersed silica sphere solution was poured into a beaker and stirred for 10 minutes, and the obtained solution was ultrasonically treated for 10 minutes and then poured into 100 mL of polytetrafluoroethylene liner. The inner tank was placed in a reactor, heated to 140°C, kept warm for 10 hours, and freeze-dried to obtain CuSiO x Material, CuSiO x The pore size of the material is 2-4nm and the specific surface area is 521.79m 2 g -1 .

[0025] (2) Take 100 mg of the obtained CuSiO x Disperse 10 mL of 0.5 mol / L nickel chloride solution in a 100 mL ethylene glycol oil bath, heat to 100 ° C and reflux for 30 minutes, add 5 mL of hydrazine hydrate and 5 mL of 28 wt.% ammonia water, stir evenly and let stand for 5 min, then cool to room temperature. Filter the solution and rinse it with deionized water three times, dry it and take it out, then put 100 mg of the prepared sample into a 50 mL flask, add 35 mL of deionized water and ultrasonically disperse it for 10 minutes. While magnetically stirring, add 100 mg of acetylacetonate gold. Among them, gold and CuSiO x The mass ratio of was 0.15:1. The obtained solution was dispersed by ultrasonic for 10 minutes, and 100 mg of sodium borohydride was added. After heating to 200 °C, it was filtered, washed and dried. Then the sample was dissolved in 30 mL of 1 M hydrochloric acid solution, slowly stirred for 24 h, centrifuged, washed with deionized water and ethanol several times, and freeze-dried to obtain AuNi / CuSiO xElectrocatalytic hydrogen evolution catalyst; wherein the AuNi alloy accounts for 25wt% of the total catalyst, and the mass ratio of Au to Ni in the AuNi alloy is 1:0.65, recorded as 25wt% AuNi / CuSiO x Electrocatalytic hydrogen evolution catalyst.

[0026] Example 4 An electrochemical workstation was used to carry out electrochemical testing of the catalyst.

[0027] The electrolyte solution used was 0.5M H2SO4 solution, the test temperature was room temperature, the test system was a conventional three-electrode system, the graphite rod electrode was the counter electrode, and the saturated Ag / AgCl electrode was the reference electrode. All potentials in the test results were adjusted to the potential relative to the reversible hydrogen electrode (vs. RHE). The linear sweep voltammetry (LSV) test scan rate was 5mV / s. Before the test, the electrode was subjected to cyclic voltammetry scans at a scan rate of 50mV / s for 100 times. After the linear sweep voltammetry (LSV) test was completed once, the electrode was subjected to cyclic voltammetry scans at a scan rate of 50mV / s for 1000 times, and the linear sweep voltammetry (LSV) test was performed again at a scan rate of 5mV / s. Figure 2 This is the cyclic voltammetric polarization (LSV) curve of the hydrogen evolution catalyst obtained in Example 1 of the present invention. For comparison, a commercial 20 wt% Pt / C was used for electrochemical testing under the same test conditions. Its cyclic voltammetric polarization (LSV) curve is also shown in Figure 2 In. By Figure 2 It can be seen that the mass proportion of the PtCu alloy prepared by the present invention is 25%, and the 25wt% PtCu / CuSiOx electrocatalytic hydrogen evolution catalyst with a PtCu alloy particle size of 30nm is 10mA / cm 2 The overpotential is 24 mV. After 1000 cyclic voltammetry scans, the mass proportion of PtCu alloy is still 20%, and the particle size of PtCu alloy is 20-25 nm, indicating that after 1000 cyclic voltammetry scans, part of PtCu alloy falls off from the catalyst support. 2 The overpotential is 25 mV, which is significantly better than commercial 20 wt% Pt / C, indicating that the catalyst obtained in the present invention has a higher hydrogen evolution activity at a lower Pt loading, and the catalyst has good durability and potential application value.

[0028] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0029] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This narrative method of the specification is only for clarity. Those skilled in the art should regard the specification as a whole. The technical solutions of each embodiment can also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. An electrocatalytic hydrogen evolution catalyst with an alloy as an active metal for use in the electrolysis of water to produce hydrogen, characterized in that: The catalyst comprises alloy particles and a carrier CuSiO x The alloy particle loading is 0.1-99.9% of the total mass of the catalyst.

2. The electrocatalytic hydrogen evolution catalyst according to claim 1, characterized in that Based on the catalyst, the content of the alloy is 15-30wt%.

3. The electrocatalytic hydrogen evolution catalyst according to claim 1, characterized in that Alloy is an alloy of precious metal and non-precious metal, and the mass ratio between the two is 1:0.05-1:

10.

4. The electrocatalytic hydrogen evolution catalyst according to claim 1, characterized in that Support CuSiO x The pore size is 2-4nm and the specific surface area is 500-600m 2 g -1 .

5. The electrocatalytic hydrogen evolution catalyst according to claim 3, characterized in that: Precious metals include one or more of gold, silver, platinum, ruthenium, rhodium, palladium, osmium, and iridium; non-precious metals include one or more of copper, cobalt, nickel, and iron.

6. A method for preparing the electrocatalytic hydrogen evolution catalyst according to any one of claims 1 to 5, characterized in that: The steps include: (1) Preparation of SiO2 nanospheres; (2) Add the SiO2 nanospheres prepared in step (1) into deionized water, then add copper salt, stir, heat, and keep warm for 5-20 hours, then filter, wash, and dry to obtain the product CuSiO x ; (3) The CuSiO prepared in step (2) x Dispersed in a solvent, then adding a non-precious metal precursor, stirring and heating for 1-10 hours to reduce it and load the non-precious metal on CuSiO x , then filter, wash and dry; (4) dispersing the product obtained in step (3) in deionized water, adding a noble metal precursor, stirring and heating for 1-10 hours, performing replacement reduction or adding a reducing agent to reduce the non-noble metal element to form an alloy, and then filtering, washing, and drying; (5) dispersing the product obtained in step (4) in an acid solution and stirring for 1 to 24 hours, then filtering, washing, and drying to obtain the electrocatalytic hydrogen evolution catalyst.

7. The preparation method according to claim 6, characterized in that: The preparation method of SiO2 in step (1) comprises the following steps: stirring an organic solvent, deionized water and ammonia water, adding a silicon source and stirring for 5-50 hours, then filtering, washing and drying to obtain the product SiO2; the organic solvent comprises one of ethanol, ethylene glycol and acetone; the silicon source comprises one of tetraethyl silicate, sodium silicate and ethyl metasilicate.

8. The preparation method according to claim 6, characterized in that: The non-metal precursor in step (3) includes nitrate, acetylacetonate, sulfate, hydrochloride, perchlorate of non-noble metal, and the non-noble metal precursor and CuSiO x The mass ratio is 200:1-0.02:

1.

9. The preparation method according to claim 6, characterized in that: The noble metal precursor described in step (4) includes acetylacetonate, nitrate and chloride of the noble metal.

10. The preparation method according to claim 6, characterized in that: The acid described in step (5) includes one or more of hydrochloric acid, sulfuric acid, nitric acid, perchloric acid, hypochlorous acid, and hydrofluoric acid. The solvent of the acid solution includes a mixture of one or more of water, methanol, ethanol, ethylene glycol, pentanediol, isopropanol, glycerol, acetone, and butanol. The concentration of the acid solution is 0.1-10 mol / L.

Citation Information

Cited By

  • Sea urchin-shaped Fe2O3-coated CuSiO3 catalyst and preparation method thereof

    CN121137675A

  • A sea urchin-like Fe2O3@CuSiO3 catalyst and its preparation method

    CN121137675B